LEARNING OUTCOMES OF A COMPUTER BASED TEST FOR COMPUTATIONAL THINKING BASED ON LOCAL WISDOM - Ria, Reny Refitaningsih Peby; Susilowati, Dyah (International Education Trend Issues, 2023)
Computational Thinking (CT) is an important ability in solving complex problems in the era of industrial revolution 4.0. This research aims to determine student learning outcomes in local wisdom-based computational thinking diagnostic tests in information technology research learning using CBT. This type of research is quantitative research with a descriptive approach. The sample for this research was 108 undergraduate students in Computer Science and Bachelor of Information Technology, Bumigora University. Construct validity estimation using EFA and instrument reliability using Cronbach Alpha. Data collection techniques and instruments use a two tier diagnostic test with CBT. The data analysis technique uses the average test. The results of this study show that the average student score on the local wisdom-based CT diagnostic test using CBT is in the high category. Thus, student learning outcomes in CT ability are high.